Analisis Pola Seismisitas Berdasarkan Nilai B-Value di Wilayah Laut Flores - Rosidi, Fachrul; Azisyarlina, Dwi; Wati, Lia Nurfitriana; Munir, Rahmiati; Haryono, Arif; Imran, Muh (GEOSAINS KUTAI BASIN, 2025)
The Flores Sea, located within Indonesia's territorial waters, is an area with high volcanic and seismic activity due to its position within the Pacific Ring of Fire. The complex movement of tectonic plates frequently triggers earthquakes in this region. This study was conducted to analyze earthquake potential in three segments of the Flores Sea area based on b-value and to examine earthquake events with magnitudes ≥ 7.4 within the period from 2000 to 2023 using Matlab and Zmap applications. From the analysis, it was found that Segment 1 has a higher potential for major earthquakes due to its low b-value. Meanwhile, Segment 2 shows a b-value below 1.19, indicating a significant potential for major earthquakes. In contrast, Segment 3 exhibits a b-value above 1.11, suggesting a lower likelihood of large-scale earthquakes. However, significant earthquakes can still occur, such as the one in Lospalos in December 2021 with a magnitude of 7.6. This demonstrates that, despite lower risk based on b-value, major earthquakes remain possible. Overall, from 2000 to 2023 in the Flores Sea region, only two events were recorded with magnitudes exceeding ≥ 7.4: one in Segment 2 with a magnitude of 7.5 in 2005, and another in Segment 3 with a magnitude of 7.6 in 2021.